The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/w10121835
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Biochar Filters for Onsite Wastewater Treatment: Effects of Biochar Type, Physical Properties and Operating Conditions

Abstract: The potential of biochar as a filter medium for onsite wastewater treatment was investigated in five sub-studies. Sub-study 1 compared pollutant removal from wastewater using pine-spruce biochar, willow biochar and activated biochar (undefined biomass) filters. Sub-study 2 investigated the effects of particle size (0.7, 1.4 and 2.8 mm) on pollutant removal using pine-spruce biochar filters. In sub-studies 3 and 4, the effects of the hydraulic loading rate (HLR; 32–200 L m−2) and organic loading rates (OLR; 5–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
(25 reference statements)
0
17
0
1
Order By: Relevance
“…Accordingly, no significant effect of the assumed higher adsorption capacity of bacteria on biochar could be observed over the whole experimental period of 70 days. Due to the high OLR of the AnBFs, which was notably higher than in comparable studies 7,8,18,19 , it can be assumed that the adsorption capacity of biochar was exhausted in an early stage of our experiment. This is supported by the fact that the main removal of E. coli in the AnBFs took place within the schmutzdecke.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Accordingly, no significant effect of the assumed higher adsorption capacity of bacteria on biochar could be observed over the whole experimental period of 70 days. Due to the high OLR of the AnBFs, which was notably higher than in comparable studies 7,8,18,19 , it can be assumed that the adsorption capacity of biochar was exhausted in an early stage of our experiment. This is supported by the fact that the main removal of E. coli in the AnBFs took place within the schmutzdecke.…”
Section: Resultsmentioning
confidence: 77%
“…Dalahmeh et al 18 used biochar filters as an on-site sewage treatment for the removal of pharmaceuticals from wastewater and found, particularly due to adsorption of persistent substances, a significant higher elimination of the investigated substances in biochar columns in comparison to the tested sand filters. Perez-Mercado et al 19 investigated the suitability of biochar filters for wastewater treatment and reported higher total nitrogen removal for biochar filters compared to sand filters. Mohanty and Boehm 20 treated stormwater with biochar augmented sand biofilters and found an improved retention of E. coli (~96%) in biochar columns compared to sand (~35%) and explained this result by higher pathogen adsorption rates on biochar particles.…”
mentioning
confidence: 99%
“…Biochar may also be used in environmental rehabilitation such as remediation of saline soils and reclamation of abandoned mine land through its high capacity for contaminant immobilization (Feng et al, 2020;Guo et al, 2016a). Biochar filters are suitable for onsite wastewater treatment (Perez-Mercado et al, 2018;Dalahmeh et al, 2020). In "green" chemistry, biochar is used as an enzyme carrier or immobilizer to increase the enzymatic activity and thermal stability (Noritomi et al, 2019;Noritomi et al, 2018;Noritomi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally produced by pyrolysis from agricultural residues, manure or wood, and characterised by having a large surface area (200-1000 m 2 /g), low density and high porosity which makes it an efficient adsorbent and good biofilm carrier (Downie et al, 2009;Enaime et al, 2020). Due to its unique properties, there is growing interest in using it as a filter medium to enhance water and wastewater quality (Perez-Mercado et al, 2018). Many studies have also demonstrated its efficiency as an adsorbent and biofilm carrier for removing organic matter, surfactants, phosphorus (P) and nitrogen (N) from onsite wastewater and greywater treatment systems (Rasheed et al, 2017;Gwenzi, 2018;Ye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%